Pengaruh konduktivitas thermal pada hot cylinder mesin stirling menggunakan energi surya terkonsentrasi - Akhmad Rizal Fanani; Muhammad Agus Sahbana; Purbo Suwandono (TURBO [Tulisan Riset Berbasis Online], 2021)
Renewable energy is one of the businesses sector that will develop rapidly after the changing economic order due to the corona outbreak. The characteristics of Indonesia's tropical climate by getting good sunlight throughout the year can be used as alternative and renewable energy. The Stirling engine is one type of external combustion engine, because combustion is carried out outside the engine using a closed regenerative cycle in which the working fluid is compressed or expanded in a separate reservoir and then distributed to drive the power piston reciprocatingly. The method developed is the use of solar energy which is concentrated by a parabolic reflector to the hot cylinder of the Stirling engine to convert heat energy into motion energy. The purpose of this study was to determine the effect of the thermal conductivity of several material specimens used in the hot cylinder of the Stirling engine including copper, stainless steel, & glass. This study uses an experimental method to describe the performance of a stirling engine prototype using various types of hot cylinder material specimens. The results showed that the gamma stirling engine using hot cylinder glass material had the best performance because with a heat conductivity of 0.78 W/mËšC it was able to drive a stirling engine with a speed of 132 rpm and a torque of 0.57 N.mm at the temperature difference between hot cylinder and cold cylinder of 88ËšC and with a thermal efficiency of 20.39%.